Effect of In–Sn Ordering on Semiconducting Properties in InSnCo3S2 – X‐ray, 119Sn Mößbauer Spectroscopy, and DFT Studies1. Issue 2 (21st November 2012) - Rothballer, Jan; Bachhuber, Frederik; Pielnhofer, Florian; Schappacher, Falko M.; Pöttgen, Rainer; Weihrich, Richard
Abstract: The crystallographic and electronic structure of shandite‐type InSnCo3 S2 was reinvestigated. Single‐crystal and powder X‐ray diffraction, 119 Sn Mößbauer spectroscopy, and DFT studies focused on the relation between the In–Sn ordering and a recently predicted semiconductor‐to‐metal transition. One aim of the combined experimental and theoretical approach was to show how the occupation of Sn and In sites causes structural distortions. The second aim was to point out effects on the electronic structure and the relative stability of structural variants with respect to In–Sn ordering. The interpretation of both X‐ray diffraction and Mößbauer spectroscopy data by DFT calculations helped to understand the effects from a nonlocal and a local point of view. This is a starting point of materials design for various applications. Abstract : InSnCo3 S2 shows ordering of In and Sn, depending on which the compound behaves like a metal or like an insulator – as shown by combined XRD, Mößbauer spectroscopy, and DFT studies